On message recognition protocols: recoverability and explicit confirmation. (31st January 2011) - Goldberg, Ian; Mashatan, Atefeh; Stinson, Douglas R.
We look at message recognition protocols (MRPs) and prove that there is a one-to-one correspondence between stateless non-interactive MRPs and digital signature schemes. Next, we examine the Jane Doe protocol and note its inability to recover in case of a certain adversarial disruption. We propose a variant of this protocol which is equipped with a resynchronisation technique that allows users to resynchronise whenever they wish. Moreover, we propose another protocol which self-recovers in case of an intrusion. This protocol incorporates the resynchronisation technique within itself. Further, we enumerate all possible attacks against this protocol and show that none of the attacks can occur. Finally, we prove the security of the new protocol and its ability to self-recover once the disruption has stopped. Finally, we propose an MRP which provides explicit confirmation to the sender on whether or not the message was accepted by the receiver.